Visit‐to‐visit HbA1c variability and systolic blood pressure (SBP) variability are significantly and additively associated with mortality in individuals with type 1 diabetes: An observational study. Issue 4 (18th January 2018) - Wightman, Stuart S.; Sainsbury, Christopher A. R.; Jones, Gregory C.
Abstract : Aim: To investigate the relationship between variability in both visit‐to‐visit HbA1c and SBP and mortality in individuals with type 1 diabetes. Methods: The Scottish Care Information (SCI) Diabetes dataset was used to identify 5952 individuals with type 1 diabetes for inclusion in this observational study. The SCI‐Diabetes dataset allowed access to blood pressure values, HbA1c readings, demographic information and mortality rates for all study participants. Participants were dichotomized to above and below median values for both HbA1c coefficient of variation (CV) and SBP CV, thus dividing participants into 4 cohorts for survival analysis. Survival analysis was carried out over 1430 days. A Cox proportional hazard model was used to allow comparison of mortality between the 4 cohorts. Results: Of the 5952 patients, death occurred in 416. CV for both HbA1c and SBP were significantly associated with mortality. The median values for HbA1c CV and SBP CV were 8.0 and 8.1, respectively. The hazard ratio for high HbA1c CV only ( P = .0015) was 1.78 ± 0.36. The hazard ratio for high SBP CV only ( P = .0018) was 1.69 ± 0.33. The hazard ratio for both high HbA1c CV and high SBP CV ( P < .00001) was 2.37 ± 0.32. Conclusions: Our findings demonstrate that variability of both HbA1c and SBP is significantly and additively associated with mortality in individuals with type 1 diabetes. The variability of these parameters might be useful for risk stratification and is a potential target for future interventional studies.